Development of In-house Chest Phantom for Pediatric Cancer Cases (International Journal of Scientific Research in Science and Technology, 2025)
This study aims to develop an in-house phantom that can more cheaply represent pediatric lung cancer cases. The materials used in this study were polymethyl methacrylate (PMMA) as a substitute for soft tissue, polyurethane (PU) foam as a substitute for lung tissue, and calcium carbonate as a replacement for rib bones. Cancer or nodules were represented using beeswax. The phantom evaluation was conducted using IndoQCT software, with parameters such as CT number, noise, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR). The CT numbers of cancer/nodule, normal lung, soft tissue, and bone for the in-house phantom are -217 to -117, -979, 80, and 871 HU, respectively. As comparison, the CT number of cancer/nodule, normal lung, soft tissue, and bone for the real patients are -141 to -103, -906, 73, and 743 HU, respectively. These findings indicate that the CT number, noise, SNR, and CNR values for the substitute materials used in the in-house phantom closely resemble the imaging values of patients with cancer/nodules. Thus, the materials used can effectively represent human tissue substitutes.